1. The problem statement, all variables and given/known data Alright, so I've given this guy a few cracks, and I think I'm close to it, but apparently I'm not right, so here's how it goes. Simple in concept. A meteor moves toward the solar system with speed v0 in a direction such that it would miss the sun by a distance d if it were not attracted by the sun's gravitational force. Denote the mass of the sun by M. Find the distance b of the meteor from the sun at the point of closest approach in terms of v0, d, and M (and G, the gravitational constant). http://img515.imageshack.us/img515/8376/lg0704figgx8.jpg [Broken] http://g.imageshack.us/img515/lg0704figgx8.jpg/1/ [Broken] 2. Relevant equations They effectively give me a few formulas in the helper questions provided: The momentum and energy are conserved Initial energy = 1/2mv0^2 Final energy = 1/2mV^2 - GMm/b Initial Momentum = mv0d Final Momentum = mVb Where V=the final velocity of the object at point b 3. The attempt at a solution I feel like the error here is most likely in my algebra, as I'm having a ton of troble easily isolating b. But here are the ways I've tried so far: I always start with the equations: 1/2mv0^2 = 1/2mV^2 - GMm/b and mv0d = mVb. I then cancel out all the m's and multiply out the 2 in the top one to get: v0^2 = V^2 - 2GM/b and v0d = Vb From this point, I'll either solve for b in the top or solve for V in the bottom. If I solve for b in the top, I get: V^2 - v0^2 = 2GM/b, b = 2GM/(V^2 - v0^2) Then I would solve for V in the bottom one: V = v0d/b Subbing that in gets b = 2GM/((v0d/b)^2 - v0^2) And this is where I think I go wrong...trying to get b out of this. I've tried rearranging the equation to bring all the b's to one side, I've tried resubstituting stuff...most recently I tried quad formula: I factored out the v0's on the bottom: 2GM/((v0^2)(d^2/b^2-1)) = b b(d^2/b^2 - 1) = 2GM/v0^2 d^2/b - b = 2GM/v0^2 d^2 - b^2 = 2GMb/v0^2 b^2 + 2GMb/(v0^2) - d^2 = 0 then, using 1 as (a), 2GM/v0^2 as (b) and -d^2 as (c), I did quad form and got: (-2GM/(v0^2)+sqrt((2GM/v0^2)^2-4d^2))/2 or http://img395.imageshack.us/img395/482/e5a7daf972eacf000cabb54ld4.gif [Broken] http://g.imageshack.us/img395/e5a7daf972eacf000cabb54ld4.gif/1/ [Broken] But that was not correct I'm officially stumped by this point...I've taken 4 cracks at it, to no avail. Am I setting up the formulas incorrectly, or am I just screwing up on the algebra over and over?